Radiocarbon dates, biomarker concentrations and compound-specific isotopes data of sediment core GeoB7702-3 - Meyer, Vera D; Pätzold, Jürgen; Mollenhauer, Gesine; Castañeda, Isla S; Schouten, Stefan; Schefuß, Enno (PANGAEA, 2024)
The dataset comprises radiocarbon dates of planktic foraminifera and hydrogen and carbon stable isotopic compositions (δD and δ13C) of high molecular weight n-alkanoic acids (leaf-wax biomarkers) in a sediment core from the eastern Mediterranean (GeoB7702-3). The records cover the past 18 ka. In this dataset new radiocarbon dates of planktic foraminifera are combined with previously published radiocarbon dates of planktic foraminifera (Castañeda et al., 2010; doi:10.1594/PANGAEA.736913) in order to produce a new age depth model. Next to a compilation of all radiocarbon dates used for the updated chronology the new age-depth model for the core are provided. The δD signature of high molecular weight n-alkanoic acids is reported as measured values (corrected for methylation (δD)) and as ice-volume corrected values (δDwax). Moreover, δD is converted into δD of precipitation by correcting it for past changes in the relative contributions of C3 versus C4 plants and ice-volume changes (δDp-vc-ic). In addition to δDp-vc-ic values of high molecular weight n-alkanoic acids we include the δDp-vc-ic of high molecular weight n-alkanes (leaf-wax lipid). The latter is calculated based on original δD data from Castañeda et al. (2016) (doi:10.1594/PANGAEA.858559). The reported δ13C-values of high molecular weight n-alkanoic acids are corrected for methylation (δ13Cwax). Based on δ13Cwax the relative contribution of C4 plants to the pool of high molecular n-alkanoic acids is calculated (%C4). It is also provided for high molecular weight n-alkanes which is calculated using original δ13Cwax-data from Castañeda et al. (2016) (doi:10.1594/PANGAEA.858559). Next to the isotopic compositions we also report concentrations of n-akanoic acids and n-alkanes.
Keywords: African Humid Period; Carbon isotopes; hydroclimate; Hydrogen isotopes; leaf-wax biomarkers; Nile River; Westerlies